Polarization lidar at summit, Greenland, for the detection of cloud phase and particle orientation - Neely, R. (R. R. Neely III) (authoraut); Hayman, Matthew (Matthew Hayman) (authoraut); Stillwell, R. (R. Stillwell) (authoraut); Thayer, J. (J. P. Thayer) (authoraut); Hardesty, R. (R. M. Hardesty) (authoraut); O'Neill, M. (M. O'Neill) (authoraut); Shupe, M. (M. D. Shupe) (authoraut); Alvarez, C. (C. Alvarez) (authoraut) (Journal of Atmospheric and Oceanic Technology)
Accurate measurements of cloud properties are necessary to document the full range of cloud conditions and characteristics. The Cloud, Aerosol Polarization and Backscatter Lidar (CAPABL) has been developed to address this need by measuring depolarization, particle orientation, and the backscatter of clouds and aerosols. The lidar is located at Summit, Greenland (72.6°N, 38.5°W; 3200 m MSL), as part of the Integrated Characterization of Energy, Clouds, Atmospheric State, and Precipitation at Summit Project and NOAA's Earth System Research Laboratory's Global Monitoring Division's lidar network. Here, the instrument is described with particular emphasis placed upon the implementation of new polarization methods developed to measure particle orientation and improve the overall accuracy of lidar depolarization measurements. Initial results from the lidar are also shown to demonstrate the ability of the lidar to observe cloud properties.